Highly uniform microfluidic electroless interconnections for chip stacking applications. (20th April 2021) - Hung, H.T.; Ma, Z.D.; Shih, P.S.; Huang, J.H.; Kao, L.Y.; Yang, C.Y.; Renganathan, Vengudusamy; Kao, C.L.; Hung, Y.C.; Kao, C.R.
Abstract: The high uniformity microfluidic electroless bonding processes of Nickel (Phosphorus) (Ni(P)), Copper (Cu), and Gold (Au) were achieved for the vertical interconnection between Cu pillars at very low bonding temperature and without pressure. Three flow patterns of electroless bonding system were investigated and applied which includes continuous flow, intermittent flow, and intermittent oscillatory flow. Atomic hydrogen and hydrogen gas bubbles were founded to be the cause of skip-plating and extraneous plating in the microchannel. The important parameters influencing the flow patterns are founded to be flow rate, stay time, and reverse flow and were investigated to deal with the intermediate and by-products so as to achieve a high degree of uniformity in the bonding. Furthermore, the effect of the geometry of Cu pillar on the formation of void and seam within the interconnection was included as well.